POETIC FUNCTIONS OF PHONETIC UNITS USED IN DEVOTIONAL CREATIVITY - Abdullayeva Manzura Nasibullo qizi (Research Focus International Scientific Journal, 2024)
In this brief research study, the poetic functions of phonetic units used in the works of the poet Hayratiy are analyzed. It is demonstrated through examples that various word units emerge through the combined repetition of vowels and consonants among phonopoetic expressions.